2006
DOI: 10.1080/00221546.2006.11778928
|View full text |Cite
|
Sign up to set email alerts
|

Salvaging “Academic Disaster Areas”: The Black College Response to Christopher Jencks and David Riesman's 1967 Harvard Educational Review Article

Abstract: During my junior year at Grambling College, the campus was roiled by the release of an article in Harvard Educational Review. [One of the articles] launched a broadside attack against Black colleges essentially questioning whether these hard-fought for institutions deserved to exist. The article's publication caused the handful of whites on the faculty to become noticeably uncomfortable and regrettably led some of the colleagues and students to question their fealty to Grambling. (Schexnider, 2003, 128) Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Observers often differ regarding their strengths, weaknesses, and even their relevance (Gasman 2006). As researchers ourselves with informed opinions on a variety of issues surrounding HBCUs, our goal here is not to satisfy or even address the breadth of concerns related to these schools.…”
Section: Introductionmentioning
confidence: 99%
“…Observers often differ regarding their strengths, weaknesses, and even their relevance (Gasman 2006). As researchers ourselves with informed opinions on a variety of issues surrounding HBCUs, our goal here is not to satisfy or even address the breadth of concerns related to these schools.…”
Section: Introductionmentioning
confidence: 99%
“…HBCUs in this study found themselves under strained financial circumstances, which were exacerbated by unstable enrollment and declines in federal and state funds (Boland and Gasman 2014). Although HBCUs are unique for their historic mission of educating those from Black communities, their membership in the organizational field of US postsecondary education suggests they are exposed to external pressures similar to non-HBCU institutions (Gasman 2006;Toma 2012). By exploring the relationship between the institutional motivations and the consequences for investing in STEM education, this study sought to understand how these HBCUs respond to organizational pressures.…”
Section: Discussionmentioning
confidence: 99%
“…These are important considerations as HBCUs are a result of and maintained by an unequal system. Because they are dedicated to educating those from Black communities, HBCUs are often perceived as inferior institutions that confer inferior degrees (Gasman, 2006). Histories of American higher education (Kendi 2012;Rojas 2007;Thelin 2011) have documented extensively the vicious physical and symbolic violence against any form of Black expression in the academy.…”
Section: Historically Black Colleges and Universities: Race And Legitmentioning
confidence: 99%
“…Interestingly, when time came to evaluate the effectiveness of Black colleges, scholars, policy makers, and donors often used " large " and " prestigious " institutions as benchmarks against which Black colleges could be measured ( Gasman, 2006 ).…”
Section: Reasons For Not Giving To Black Collegesmentioning
confidence: 99%